VAGINAL DELIVERY OF A RARE MONSTER (SYNCEPHALO THORACOPAGUS QUADRIBRACHIUS QUADRIPUS) IN A BUFFALO - GHUMAN, S P S; HONPARKHE, M (The Indian Journal of Animal Reproduction, 2023)
Partial fetotomy was carried out for delivery of a fully developed syncephalo-thoracopagus quadribrachius quadripus monster in a multiparous Murrah buffalo. The monster had twin bodies which were fused from head to thorax. There was partial duplication of the face (four nostrils and two upper jaws separated by a single enlarged lower jaw), one head, two eyes, four ears and eight limbs.